Waqf Blockchain Untuk Pengadaan Alat Kesehatan Penanganan Covid-19: Studi Konseptual (UIN Sunan Kudus, 2020)
The research aims to develop a scheme of waqf fund management based on the blockchain system. This system is used for the procurement of personal protective equipment as an effort to prevent the Covid-19 pandemic in Indonesia. The approach method used qualitative research, based on the basis of consideration of data and facts related to the spread of pandemic Covid-19 requires in-depth analysis. The renewal of the schemes and instruments of the waqf fund with blockchain endowments that can be applied in specific social projects is an important added value. The results of this research are the optimization of waqf funds, which starts from the process of collecting, managing, developing, and distributing waqf funds for specific social activities that can be targeted. The target of this research is the transparency of the management of waqf funds can be better so that sharia-based financial instruments can contribute greatly to the handling of Covid-19.